Pacientes con cefalea y su relación orgánica con la tomografía computarizada que acuden al Hospital de Especialidades Eugenio Espejo de la ciudad de Quito. - Calero Armijos, Amelia Beatriz (2016)
The headache is first of the main reasons for medical appointment in Primary Care and Neurology; It is considered a real disease or syndrome (Cephalic disorder) for the multiple and varied etiologies since organics and functionals. This research paper is titled: "The patients with headache and the organic relationship with the Computed Tomography scan who come to the <<Hospital de Especialidades Eugenio Espejo>> of the Quito city"; this research was develop in order to achieve the following aims: to know the relationship between headache and organic findings detected by computed tomography, to identify cases by age and sex, to differentiate the findings by region and their relationship with diagnoses. The research was cross with a total of 130 patients in the period from January to June 2016 which they met the criteria for inclusion and exclusion, the data was obtained from Imaging Service through a data- collection analyzed by simple and inferential statistics. The results reflected three significant events: First, a low percentage of patients showed intracranial lesions 21,5%, secondly, the most common age range was 51 to 60 years that’s mean the 10,0%, finally, the hyperintensities murals in the carotid arteries were the most common tomographic findings 25,0% associated with the diagnosis of Primary Intracranial Atherosclerosis. Among the important contributions stand out the proposal of use of the criteria established for to apply CT scan in patients with headache in order to avoid unnecessary radiation and recognize the warning signs for a correct diagnosis and appropriate clinical and therapeutic management of these patients. Keywords: Headache, Computed Tomography scan, Primary Intracranial Atherosclerosis